ANALYSIS LEGAL PROTECTION OF CONTRACT WORKERS FOR REPEATED EMPLOYMENT RELATIONS - M. Alvin Sofiandy; Wiwik Afifah (SYNTIFIC, 2026)
Background. Fixed-term contracts that are often extended lead to a continuous employment relationship, creating legal concerns about employment status. The disparity in negotiating power between workers and employers results in a conflict between labor protection and corporate flexibility. Research Purpose. This study analysis legal protection of contract workers in repeated employment relations, particularly the renewal or extension of fixed-term employment agreements and its impact on legal certainty, job security, and workers’ rights. Research Method. Using a qualitative case study approach, this research explores how repeated contract practices are experienced and interpreted by workers, employers, labour union actors, and labour law practitioners. Data were collected through semi-structured interviews, limited observation, and documentation, then analyzed thematically to identify recurring patterns. Findings. The findings reveal three main themes: uncertainty of employment status, unequal bargaining position, and weak enforcement of compensation and protection mechanisms. Although repeated fixed-term contracts may formally comply with written employment requirements, they can weaken substantive protection when used for continuous and structurally necessary work. This study contributes to socio-legal scholarship by showing that labour protection should be assessed not only through statutory rules, but also through enforcement practices and workers’ lived experiences. Conclusion. The study imply the need for stronger labour inspection, clearer contract transparency, and improved legal literacy for contract workers.